Comparison of gingival display in smile attractiveness among restorative dentists, orthodontists, prosthodontists, periodontists, and laypeople - Pinzan-Vercelino, Célia Regina Maio; Costa, Ana Carla Souza; Ferreira, Meire Coelho; Bramante, Fausto Silva; Fialho, Melissa Proença Nogueira; Gurgel, Júlio de Araújo [UNESP] (Elsevier, 2019)
Statement of problem: Multidisciplinary treatment needs a common goal, and dentists should understand the esthetic perception of laypeople and the other specialists involved. Such information is sparse. Purpose: The purpose of this cross-sectional study was to compare the influence of gingival display on perceived smile esthetics among restorative dentists, orthodontists, prosthodontists, periodontists, and laypeople. Material and methods: Photographs of the smiles of 2 volunteers (1 female and 1 male)were manipulated on a computer to produce gingival exposure of 1, 3, and 5 mm and central incisor coverage of 3 and 5 mm. The images were evaluated by using a 100-mm visual analog scale by 155 raters divided into 5 groups (restorative dentists, orthodontists, prosthodontists, periodontists, and laypeople). Results: The dental specialists, mainly orthodontists and periodontists, were more sensitive about alterations in gingival display than the laypeople. For the female smile, higher mean scores were attributed to 1 mm of gingival exposure by all groups of raters. For the male smile, 3 mm of central incisor coverage received higher mean scores, except for the laypeople, who considered gingival display of 1 mm to be more attractive. For both smiles, 5 mm of gingival display was judged to be the least attractive. Conclusions: Considering the differences in opinion between dental specialists and laypeople and the acceptable variations in gingival display, the preferences of patients should be considered in the diagnosis and treatment decision-making process.